Comparative Studies on Antioxidant Activity of Ten Medicinal Plants Collected From the Ilam District of Nepal - Kalauni, Surya Kant; Niraula, Muna; Thapa, Prakash; Pathak, Ishwor (Nepal Journal of Science and Technology, 2021)
Methanol extracts of ten medicinal plants collected from Ilam district were prepared and a preliminary phytochemical screening was performed. Phytochemical test revealed that selected plant samples contain alkaloids, flavonoids, terpenoids, glycosides, quinones, reducing sugars, coumarin, polyphenols, and saponins. The antioxidant properties of ten samples were evaluated by using DPPH free radical scavenging assay and their inhibitory concentration for 50% inhibition (IC50 values) for antioxidant properties were calculated. Among all ten studied samples, IC50 values of extracts of barks of Atrocarpus lakoocha (41.42±3.1 µg/mL) and flowers of Woodfordia fructicosa (41.89±2.5 µg/ mL) were very close to that of standard ascorbic acid (38.74±2.5 µg/mL). Similarly, flowers of Rhododendron arboreum (45.55±2.2 µg/mL), roots of Vetiveria zizanoids (46.22±2.0 µg/mL) and rhizomes of Mirabilis jalapa (48.99±3.0 µg/mL) also showed strong activity against DPPH free radicals. These results showed that these plants could be the potential sources of natural antioxidants in the food and/or pharmaceutical industry